PENGGUNAAN PEMBOBOTAN MODEL BLACK-LITTERMAN DALAM MENENTUKAN VALUE AT RISK PADA PORTOFOLIO INVESTASI - Eka Swastika AP; Johannes Kho; Rolan PanePENGGUNAAN PEMBOBOTAN MODEL BLACK-LITTERMAN DALAM MENENTUKAN VALUE AT RISK PADA PORTOF (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses the use of the Black-Litterman weighting in determining the value at risk in the investment portfolio. Black-Litterman model obtained through sampling theory approach is used to determine the weight of each portfolio asset. Based on theweight of assets of the Black-Litterman obtained standard deviation Black-Litterman portfolio is used in the calculation of Value at Risk in the Black-Litterman portfolio.